THE EFFECT OF EXTERNAL AND INTERNAL STIMULI ON IMPULSIVE PURCHASING AT HYPERMART MANADO - Pinatik, Glandy (Universitas Sam Ratulangi, 2013)
ABSTRACT Â Impulsive purchasing is an interesting phenomenon that has been a concern of many researchers to analyze. Manado is a city that has consumptive customers in it. Consumptive behavior is related to impulsive purchasing where the customers make unplanned purchases. The purpose of this research is to analyze the effect of external (shop environment, shop staff, integrated marketing communication) and internal (emotional and cognitive estimation) stimuli on impulsive purchasing. Theories that support this research are shop environment, shop staff, integrated marketing communication, emotional and cognitive estimation, hedonic motives, involved into the fashion, and impulsive purchasing. The population observed is people who have purchased impulsively at Hypermart Manado with sample size as many as 163 respondents. This research used quantitative analyze by using questionnaires and used Multiple Regression Analysis. The conclusion is shop environment, shop staff, integrated marketing communication, emotional and cognitive estimation, hedonic motives, and involved into the fashion influence impulsive purchasing both simultaneously and partially. This research suggests that hedonic motives and involved into the fashion are the most influencing variables to impulsive purchasing of the customers at Hypermart Manado. Both hedonic motives and involved into the fashion are included into internal stimuli which means that the impulsive purchasing behaviour of the customers of Hypermart Manado mostly comes from the inside of the customers.